Supplier Selection and Optimization of Supply Chains - Mujkić, Zlatan; Qorri, Ardian; Kraslawski, Andrzej; Gashi, Saranda (International Journal of Management and Sustainability, 2019)
Supplier selection is one of the most important components of supply chain management. The main objective of this exercise is to select best suppliers based on different criteria. Those criteria are often closely related with sustainability and are set by the decision-maker. Hence, the objective of this paper is to integrate sustainability and decision-making. The sustainability aspect of the model includes economic, environmental and social dimensions and strategic level of decision-making criteria. The methodology used in this paper is mathematical modeling and the problem is formulated as mixed integer linear programming. The integration of sustainability and supplier selection is presented on an illustrative example of a bio-fuel supply chain. The best multi-objective solution is obtained using the weighting sum method. The study indicates that the integration of several sustainability aspects and supplier selection can be useful for decision making process. The main contribution of this work is the integration of supplier selection with the sustainability of supply chains.